Pilotski prevzem video posnetkov in digitalnih fotografij - Majerič Kekec, Nataša (Moderna arhivistika, 2021)
The article presents the pilot ingest of video clips and digital photographs created at the Ptuj City Theatre. It outlines the appraisal process, the preparation of the inventory and the creation of additional professional technical instructions by the Historical Archives in Ptuj.
Keywords: digital photographs; digitalna fotografija; Mestno gledališče Ptuj; Ptuj City Theatre; video clips; video posnetki